2022
DOI: 10.1155/2022/7857158
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of the Donor Site and Complication Rates of Breast Reconstruction with Autologous Abdominal Flaps: A Systematic Review and Meta-Analysis

Abstract: Background. Numerous studies have evaluated the use of autologous abdominal tissue for breast reconstruction; nevertheless, complications and donor site morbidity rates vary significantly. The study aims to compare the literature regarding morbidity of the donor site and complication rates of breast reconstruction with autologous abdominal flaps. Methods. The databases of MEDLINE, EBSCO, Scopus, Wiley Library, and Web of Sciences were searched for studies that compared different flaps in terms of complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This includes early complications within 30 days as well as later sequelae such as surgical correction of abdominal bulge or hernia. Traditional free TRAM flaps yielded the largest abdominal donor-site morbidity and have largely fallen out of favor for DIEP flaps, which are less likely to create hernias and bulging given increased preservation of the rectus abdominus 28–30 . With inclusion of mesh for donor-site repair, Wan et al 30 showed a reduction in hernia and bulge rates for free and muscle-sparing TRAM flaps to approximately 4%, akin to DIEP flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes early complications within 30 days as well as later sequelae such as surgical correction of abdominal bulge or hernia. Traditional free TRAM flaps yielded the largest abdominal donor-site morbidity and have largely fallen out of favor for DIEP flaps, which are less likely to create hernias and bulging given increased preservation of the rectus abdominus 28–30 . With inclusion of mesh for donor-site repair, Wan et al 30 showed a reduction in hernia and bulge rates for free and muscle-sparing TRAM flaps to approximately 4%, akin to DIEP flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional free TRAM flaps yielded the largest abdominal donor-site morbidity and have largely fallen out of favor for DIEP flaps, which are less likely to create hernias and bulging given increased preservation of the rectus abdominus. [28][29][30] With inclusion of mesh for donor-site repair, Wan et al 30 showed a reduction in hernia and bulge rates for free and muscle-sparing TRAM flaps to approximately 4%, akin to DIEP flaps. Even 4% is significant and has driven some surgeons to use mesh for extra support with DIEP flaps, 31,32 which has ultimately become common practice at our institution as well.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9]11,13,14,30,33,36,41,[43][44][45][46][47][48][49][50][51][52][54][55][56][57][58][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] However, the occurrence of infection in DIEP flaps is infrequent, with a recent meta-analysis reporting a donor site infection rate of 4.79%. 77 Mechanistically, ciNPWT acts as a barrier that prevents contamination of the surgical site with bacteria before reepithelization, encourages drainage of excess interstitial fluid, increases lymphatic flow, improves blood flow, and induces angiogenesis, theoretically decreasing the risk of infection and expediting healing. 78 In addition, wound dehiscence and infection often occur together and are often reported alone even when they are both present.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Several studies have provided evidence to support this theory, demonstrating a lower incidence of postoperative donor site complications in DIEP flap reconstruction compared with more traditional methods of autologous tissue transfer, such as TRAM flap variations. [7][8][9][10][11] Despite this lower incidence, the development of hernia and bulge following DIEP flap reconstruction is still a common occurrence, reported in more than 7% and 33% of patients who undergo this procedure. 12 Optimal techniques for abdominal fascial closure that minimize the incidence of local complications are a subject of controversy and practice variation in the plastic surgery community.…”
Section: Introductionmentioning
confidence: 99%